The wonder of dolphins - Ritchie, Rita; Corrigan, Patricia; Nicklin, Flip; McGee, John F. (Milwaukee, Wis. : Gareth Stevens Publishing, 1996)
Text and photographs introduce some of the thirty-nine different kinds of dolphins.
Includes index.
Includes glossary.
4-8
Keywords: Dolphins